Anxiety, Self Concept and Meaning of Life Patients Post Stroke Earning Age: (Qualitative Study on Post-Stroke Patients in Lemper Village, Pademawu Sub-district, Pamekasan District) - Nur Iszakiyah; Byba Melda Suhita; Sandu Siyoto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Patient post stroke should be able to immediately rise, preparing herself to return activity according to limit its ability, this matter so that stroke patient can immediately recover and avoid from condition causing disability. This study aims to analyze the level of anxiety, self-concept, and meaning of life in post-stroke patients in Lemper Village Working Area Puskesmas Pademawu Pamekasan District. Qualitative methods with case study approaches, which explore a problem with detailed constraints, have deep data retrieval, and include multiple sources of information. This study is limited by time and place as well as cases studied in the form of programs, events, activities or individuals. The results of this study identified four main themes: (1) Anxiety Level of Post-Stroke Patients Age of Productive (2) Self-concept of Post-Stroke Patients Productive Age (3) Meaning of Life Post-Stroke Patients Productive Age (4) Effort / Motivation Patients Post Stroke Productive Age in Improving Quality of Life. A false understanding will lead to adaptive malal coping mechanisms and correct understanding likely to lead to adaptive coping mechanisms. The meaning of life is produced by a combination of self-concept and experience. Experience will affect the self concept, the hypothesis that appears is the healing of stroke patients will increase the meaning of life of stroke patients.